Radioimmunotherapy with an (211)At‐labeled anti–tissue factor antibody protected by sodium ascorbate - Takashima, Hiroki (Cancer Sci, 2021)
Tissue factor (TF), the trigger protein of the extrinsic blood coagulation cascade, is abundantly expressed in various cancers including gastric cancer. Anti‐TF monoclonal antibodies (mAbs) capable of targeting cancers have been successfully applied to armed antibodies such as antibody‐drug conjugates (ADCs) and molecular imaging probes. We prepared an anti‐TF mAb, clone 1084, labeled with astatine‐211 ((211)At), as a promising alpha emitter for cancer treatment. Alpha particles are characterized by high linear energy transfer and a range of 50‐100 µm in tissue. Therefore, selective and efficient tumor accumulation of alpha emitters results in potent antitumor activities against cancer cells with minor effects on normal cells adjacent to the tumor. Although the (211)At‐conjugated clone 1084 ((211)At‐anti‐TF mAb) was disrupted by an (211)At‐induced radiochemical reaction, we demonstrated that astatinated anti‐TF mAbs eluted in 0.6% or 1.2% sodium ascorbate (SA) solution were protected from antibody denaturation, which contributed to the maintenance of cellular binding activities and cytocidal effects of this immunoconjugate. Although body weight loss was observed in mice administered a 1.2% SA solution, the loss was transient and the radioprotectant seemed to be tolerable in vivo. In a high TF–expressing gastric cancer xenograft model, (211)At‐anti‐TF mAb in 1.2% SA exerted a significantly greater antitumor effect than nonprotected (211)At‐anti‐TF mAb. Moreover, the antitumor activities of the protected immunoconjugate in gastric cancer xenograft models were dependent on the level of TF in cancer cells. These findings suggest the clinical availability of the radioprotectant and applicability of clone 1084 to (211)At‐radioimmunotherapy.